Gas barrier laminate and packaging material

The gas barrier laminate addresses the challenge of adhesion and gas barrier properties in recyclable packaging by optimizing the surface properties of the inorganic layer and using a water-soluble polymer layer, resulting in enhanced performance for packaging materials.

JP7666764B1Active Publication Date: 2025-04-22DIC CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024561636
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-06-06
Publication Date
2025-04-22
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

Existing gas barrier laminates face challenges in achieving good adhesion and maintaining gas barrier properties when a plastic film like olefin is combined with a general-purpose inorganic oxide layer, especially in recyclable packaging materials.

Method used

A gas barrier laminate is developed with a substrate layer having an inorganic layer on at least one surface, where the static contact angle of water and/or the surface free energy of the inorganic layer is optimized to enhance adhesion with a water-soluble polymer layer, and the laminate is manufactured using treatments like corona, ozone, plasma, or UV irradiation.

Benefits of technology

The laminate achieves improved adhesion and maintains excellent gas barrier properties, making it suitable for recyclable packaging materials while ensuring the integrity of the packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666764000001
    Figure 0007666764000001
  • Figure 0007666764000002
    Figure 0007666764000002
  • Figure 0007666764000003
    Figure 0007666764000003
Patent Text Reader

Abstract

A gas barrier laminate and packaging material comprising: (A) layer (A) made of a substrate having an inorganic layer formed on at least one surface thereof; and (B) layer (B) containing a water-soluble polymer, wherein in the layer (A), the surface on which the inorganic layer is formed has a static contact angle with water at 25° C. of 20 degrees or more and 80 degrees or less, and / or the surface on which the inorganic layer is formed has a surface free energy of 41 mN / m or more and 75 mN / m or less. The inorganic layer in the layer (A) is preferably formed by either a vapor deposition process or a sputtering process, and is preferably formed from one or more inorganic substances selected from the group consisting of aluminum oxide, silicon oxide, aluminum, zinc oxide, and magnesium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gas barrier laminate and a packaging material obtained by using the gas barrier laminate. [Background technology]

[0002] Packaging materials used for packaging food, daily necessities, medicines, etc. are required to have functions such as strength, resistance to cracking, and gas barrier properties in order to protect the contents from shocks received during distribution, deterioration due to oxygen and moisture, etc. As a laminated film having a gas barrier function, for example, a gas barrier laminated film is known in which a vapor deposition layer made of an inorganic compound such as aluminum oxide is used as a first layer, and a coating agent mainly composed of a water-soluble polymer and an aqueous solution containing at least one of (a) one or more alkoxides and / or their hydrolysates or (C) tin chloride, or a water / alcohol mixed solution, is applied and dried by heating, forming a gas barrier coating film as a second layer. (See, for example, Patent Document 1). However, since it is difficult to satisfy the required functions with one type of material, a laminated body in which different types of polymer materials are bonded together is widely used as a packaging material. In order to provide all the functions required for a packaging material to be distributed, the gas barrier film disclosed in Patent Document 1 is often made into a packaging material by, for example, laminating a heat-sealable thermoplastic resin layer or a printed layer on the gas barrier coating layer or on the substrate 2, or by laminating a plurality of resins via adhesive layers (see paragraph 0029 of Patent Document 1).

[0003] On the other hand, in recent years, there has been a demand for packaging materials that are not only functional, but also recyclable. There are voices saying that laminated films made of different resins that are made solely with functionality in mind will lower the quality of recycled plastics, and so there are hopes for laminated films made of the same resin type, for example packaging materials made only of olefin-based resins, as recyclable packaging materials.

[0004] As a gas barrier film made only of an olefin-based resin, for example, a gas barrier film is disclosed that comprises a polyolefin film layer of a first substrate, a polyolefin film layer of a second substrate, and a polyolefin film sealant layer in this order, and the polyolefin film of the first substrate layer or the second substrate layer has an inorganic oxide layer on at least one surface, and exhibits a specific heat shrinkage rate, so that even if the main component is a polyolefin-based film, a laminate that can be subjected to high-temperature retort treatment when made into a packaging bag can be obtained (see, for example, Patent Document 2). Here, Patent Document 2 describes that it is preferable to provide an anchor coating agent such as a polyester-based polyurethane resin or a polyether-based polyurethane resin between the polyolefin film and the inorganic oxide layer in order to improve the adhesion of the olefin-based resin, which has poor adhesion (see paragraphs 0022-0023 of Patent Document 2). However, this method requires a step of applying an anchor coating agent before providing an inorganic oxide layer on the polyolefin film, and is therefore not suitable for obtaining a recyclable packaging material having gas barrier properties by combining, for example, a general-purpose plastic film such as an olefin film having an inorganic oxide layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 2790054 [Patent Document 2] JP 2021-20391 A Summary of the Invention [Problem to be solved by the invention]

[0006] When a coating agent is laminated on an inorganic oxide layer formed on the surface of an olefin or other plastic film, good adhesion may not be obtained. This is thought to be due to the fact that after an inorganic oxide layer is formed on the surface of an olefin or other plastic film, it is usually wound up in a roll and stored, and during storage, additives such as antioxidants contained in the olefin or other plastic film bleed onto the film surface opposite to the inorganic oxide layer, contaminating the inorganic oxide layer that is in contact with it when it is wound up. Therefore, the object of the present invention is to provide a gas barrier laminate and a packaging material that maintain good adhesion and gas barrier properties even when combined with a general-purpose olefin or other plastic film having an inorganic oxide layer, and are suitable for obtaining a packaging material that can also be recycled. [Means for solving the problem]

[0007] That is, the present invention provides a gas barrier laminate comprising: (A) Layer (A) made of a substrate having an inorganic layer formed on at least one surface thereof; and (B) Layer (B) containing a water-soluble polymer, wherein in Layer (A), the surface on which the inorganic layer is formed has a static contact angle with water at 25°C of 20 degrees or more and 80 degrees or less, and / or the surface free energy of the surface on which the inorganic layer is formed is 41 mN / m or more and 75 mN / m or less.

[0008] The present invention also provides a packaging material comprising the gas barrier laminate described above.

[0009] The present invention also provides a method for producing the gas barrier laminate described above, comprising the steps of: step 1 of subjecting the inorganic layer of layer (A) made of a base material having an inorganic layer formed on at least one surface thereof to corona treatment, ozone treatment, plasma treatment, ultraviolet irradiation treatment, or excimer UV treatment; and step 2 of providing layer (B) containing a water-soluble polymer on layer (A), in this order. Effect of the Invention

[0010] The present invention makes it possible to provide a gas barrier laminate that maintains good adhesion and gas barrier properties even when combined with a plastic film such as an olefin film having a general-purpose inorganic oxide layer, and is also suitable for obtaining a recyclable packaging material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] ((A) A layer made of a substrate having an inorganic layer formed on at least one surface) The gas barrier laminate of the present invention has (A) a layer made of a substrate having an inorganic layer formed on at least one surface thereof (hereinafter, sometimes referred to as layer (A)). Here, the substrate used in the (A) layer is not particularly limited in terms of its material, manufacturing method, or shape as long as the effects of the present invention can be obtained, but in most cases, a film shape (sometimes called a sheet, but in the present invention, called a film) is used. Materials for these substrates include, for example, olefin-based resins such as polyethylene (PE), polypropylene (PP), cyclic olefin polymer (COP), and cyclic olefin copolymer (COC), polyester, acrylic, polycarbonate, cellulose ester, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), nylon (NY), and materials containing biomass-derived components. In particular, any film made of a thermoplastic resin mainly composed of an olefin-based resin can be used without any particular limitation. Specific examples of olefin resins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene, polypropylene (PP), ethylene-propylene copolymers, α-olefin polymers, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ethylene-acrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-ethyl acrylate copolymers, cyclic olefin resins, ionomer resins, and polymethylpentene; and modified olefin resins obtained by modifying olefin resins with acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, or other unsaturated carboxylic acids. Among these, it is preferable to use olefin-based resins such as polyethylene (PE), polypropylene (PP), cyclic olefin polymer (COP), and cyclic olefin copolymer (COC), since the effects of the present invention can be significantly obtained, and polyethylene (PE) and polypropylene (PP) are most preferable.

[0012] Examples of film names include polyethylene terephthalate (PET) film, polystyrene film, polyamide film, polyacrylonitrile film, polyethylene film (LLDPE: low density polyethylene film, HDPE: high density polyethylene film, MDOPE: uniaxially oriented polyethylene film, OPE: biaxially oriented polyethylene film), polyolefin film such as polypropylene film (CPP: non-oriented polypropylene film, OPP: biaxially oriented polypropylene film), polyvinyl alcohol film, ethylene-vinyl alcohol copolymer film, etc., and also biomass films formed from materials containing biomass-derived components are preferably used for food packaging. Biomass films are sold by various companies, and for example, sheets such as those listed in the list of biomass certified products listed in the Japan Organic Resources Association can be used.

[0013] The substrate used in Layer (A) is not particularly limited, and may be a substrate having a thickness that is normally used for packaging foods, daily necessities, medicines, etc. From the viewpoint of formability and transparency, a film having a thickness in the range of 1 μm to 500 μm is sufficient, preferably 1 μm to 300 μm, and more preferably 1 μm to 100 μm. If the thickness is less than 1 μm, the strength is insufficient, and if it exceeds 500 μm, the rigidity becomes too high, which may make processing difficult. The method for producing these substrates is not particularly limited, and they can be produced by various film-forming methods such as melt extrusion molding, solution casting molding, and calendar molding, and these may be further subjected to biaxial or uniaxial stretching treatment. Furthermore, films that have been subjected to various surface treatments as necessary may be used.

[0014] The layer (A) is a layer having a substrate layer with an inorganic layer formed on at least one side thereof, and the inorganic layer is formed on a part or the entire surface of at least one side of the substrate. The inorganic substances forming the inorganic layer are not particularly limited as long as the effects of the present invention can be obtained, but it is preferable to use one or more selected from metals and metal oxides such as aluminum oxide, silicon oxide, aluminum, zinc oxide, magnesium oxide, calcium oxide, and zirconium oxide, and it is particularly preferable to use one or more selected from aluminum oxide, silicon oxide, aluminum, zinc oxide, and magnesium oxide, because they exhibit good barrier properties.

[0015] In the layer (A) of the present invention, the method for forming the inorganic layer is not particularly limited as long as the effects of the present invention can be obtained. However, the inorganic layer can be formed by a vapor deposition process, a sputtering process, a CVD process, or a coating process. Since the inorganic layer can be formed uniformly, it is particularly preferable to use a vapor deposition process or a sputtering process.

[0016] The thickness of the inorganic layer may be within a range in which the effects of the present invention can be obtained, but is preferably in the range of 1 to 100 nm, and more preferably in the range of 3 to 80 nm.

[0017] The (A) layer may be provided with an anchor coat layer for the purpose of increasing the adhesion of the inorganic layer to the base layer. The anchor coat layer can be obtained by applying an anchor coating liquid onto the base layer and drying it. The anchor coating liquid may be a known one, for example, an anchor coating agent mainly composed of an acrylic resin, a urethane resin, a vinyl alcohol resin, an ethylene vinyl alcohol resin, or the like, or a curing anchor coating agent using an isocyanate or epoxy curing agent in combination. The thickness of the anchor coat layer may be within a range that can obtain the effects of the present invention, but is preferably in the range of 0.001 to 0.5 μm, and more preferably in the range of 0.01 to 0.4 μm. It is preferable to form the inorganic layer after providing the anchor coat layer.

[0018] The (A) layer in the present invention is characterized in that the surface on which the inorganic layer is formed has a static contact angle with water at 25°C of 20° to 80°, and / or a surface free energy of 41 mN / m to 75 mN / m. The surface (surface) having such characteristics is a surface that is highly wettable with water, in other words, a highly hydrophilic surface. Therefore, by setting the static contact angle and / or surface free energy of the surface within the above range, adhesion to the water-soluble polymer contained in the (B) layer is increased.

[0019] The upper limit of the static contact angle of the surface on which the inorganic layer is formed may be 80 degrees or less, preferably 70 degrees or less, more preferably 60 degrees or less, and even more preferably 50 degrees or less. The lower limit of the static contact angle may be at least 20 degrees, and is preferably at least 23 degrees.

[0020] On the other hand, the lower limit of the surface free energy of the surface on which the inorganic layer is formed may be 41 mN / m or more, preferably 45 mN / m or more, more preferably 48 mN / m or more, and even more preferably 50 mN / m or more. The upper limit of the surface free energy may be 75 mN / m or less, and is preferably 73 mN / m or less.

[0021] The (A) layer can be easily obtained by subjecting the inorganic layer that has been subjected to the vapor deposition or sputtering treatment to a surface hydrophilization treatment. Examples of the surface hydrophilization treatment include corona treatment, ozone treatment, plasma treatment, ultraviolet irradiation treatment (hereinafter abbreviated as UV treatment), ion treatment, radiation treatment, excimer UV treatment, ozone water treatment, flame treatment, and itro treatment, which are described in Practical Surface Modification Technology Overview (1993) edited by the Materials Technology Research Association. Among these, corona treatment, ozone treatment, plasma treatment, ultraviolet irradiation treatment, and excimer UV treatment are more preferable. These treatments can be used alone or in combination of two or more.

[0022] (Corona treatment) Corona treatment is a method for surface modification using corona discharge excited by applying a high voltage AC to a pair of electrodes under atmospheric pressure. The discharge amount in the corona treatment is not particularly limited, but is preferably about 10 to 200 W / m2 / min, and more preferably about 20 to 150 W / m2 / min.

[0023] (Ozone treatment, ozone water treatment) Ozone treatment is a method in which oxygen in the air is converted into ozone by ultraviolet (UV) irradiation, and the surface is modified in an ozone-containing atmosphere. A low-pressure mercury lamp is preferable as the UV light source. It is known that a low-pressure mercury lamp has an emission spectrum at wavelengths of about 185 nm and about 254 nm, and generates ozone with light having a wavelength of about 185 nm, and decomposes the ozone with light having a wavelength of about 254 nm to generate active oxygen. Therefore, by using a low-pressure mercury lamp, the inner surface can be efficiently subjected to hydrophilic treatment. The gas that is the source of ozone generation may be any gas that contains oxygen, and oxygen gas, dry air, etc. may be used. The pressure of the atmosphere for the ozone treatment may be either reduced pressure or atmospheric pressure. The time for the ozone treatment (UV irradiation time) is not particularly limited, but is preferably about 10 to 300 seconds, and more preferably about 20 to 180 seconds. When the surface modification treatment is carried out by an ozone aqueous solution treatment, the ozone concentration is preferably blown into an aqueous solution of normal water or hydrogen peroxide, etc. In this case, the ozone concentration is preferably 5 ppm or more, and more preferably 15 ppm or more.

[0024] (Plasma treatment) Plasma treatment is a method for modifying surfaces by utilizing plasma generated by the ionization of gas through discharge. The process gas may include nitrogen gas, argon gas, oxygen gas, helium gas, water, neon gas, xenon gas, carbon dioxide gas, hydrogen, and mixtures of these. The discharge is not particularly limited, but examples include corona discharge (high pressure, low temperature plasma), arc discharge (high pressure, high temperature plasma), and glow discharge (low pressure, low temperature plasma). Of these, glow discharge is preferred because it causes less thermal and electrical damage to the substrate.

[0025] (UV treatment) UV treatment (optical surface treatment) is a method of surface modification by directly irradiating the inner surface with ultraviolet (UV) rays with wavelengths of 300 nm or less, including excimer UV. The UV light source is a low-pressure mercury lamp using synthetic quartz, which has a high transmittance of UV rays, particularly short wavelengths. However, to prevent the generation of ozone, it is preferable to cut off ultraviolet rays with a wavelength of 185 nm.

[0026] If the static contact angle and / or surface free energy value of the surface on which the inorganic layer is formed is within a desired range before the hydrophilization treatment is performed, the hydrophilization treatment may be omitted.

[0027] From the viewpoint of recycling, it is preferable that the layer structure is as simple as possible, but from the viewpoint of distribution of the packaging material, printing is often required to display the contents of the packaging material or a description or name of the product. The substrate is often printed as well.

[0028] (Printing layer) The printing layer is a layer on which characters, figures, symbols, and other desired patterns are printed. There is no particular limitation on the printing method or printing ink, and any known printing method or printing ink can be used. Printing inks using gravure printing, flexographic printing, lithographic offset printing, inkjet recording printing, and the like are often used for the film used as the substrate. Printing inks that combine these printing methods with methods of curing with active energy rays such as ultraviolet rays (UV), LEDs, and electron beams (EB), or methods of curing with heat, and the like, are also used. In addition, depending on the solvent used, they may be referred to as water-based inks or organic solvent-based inks.

[0029] Specific examples include gravure printing ink and flexographic printing ink (in some industries, gravure printing ink and flexographic printing ink are referred to as liquid printing ink), ultraviolet-curable ink for lithographic offset printing, electron-beam-curable ink for lithographic offset printing, ultraviolet-curable ink for inkjet recording and printing, and electron-beam-curable ink for inkjet recording and printing.

[0030] The position where the printed layer printed using these inks is provided is arbitrary, and it may be provided on the first substrate, or a substrate on which a separate printed layer is provided may be one of the components of the laminate of the present invention, and the position is arbitrary. The ink may contain a resin, a colorant, and a solvent as essential components, or it may be a so-called clear ink that contains a resin and a solvent but does not substantially contain a colorant. Below, we will explain the liquid printing inks that are most commonly used for printing on films.

[0031] The resin used in the liquid printing ink is not particularly limited, and examples thereof include acrylic resin, polyester resin, styrene resin, styrene-maleic acid resin, maleic acid resin, polyamide resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-acrylic copolymer resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, polyvinyl chloride resin, chlorinated polypropylene resin, cellulose-based resin, epoxy resin, alkyd resin, rosin-based resin, rosin-modified maleic acid resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, petroleum resin, etc., and one or more of them can be used in combination. Preferably, at least one or two or more selected from polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, and cellulose-based resin are used.

[0032] Colorants used in liquid printing inks include inorganic pigments such as titanium oxide, red iron oxide, antimony red, cadmium red, cadmium yellow, cobalt blue, Prussian blue, ultramarine, carbon black, and graphite; organic pigments such as soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments; and extender pigments such as calcium carbonate, kaolin clay, barium sulfate, aluminum hydroxide, and talc.

[0033] Liquid printing inks for film printing are often organic solvent-based inks. The organic solvents used preferably do not contain aromatic hydrocarbon organic solvents. More specifically, examples of the organic solvents include alcohol-based organic solvents such as methanol, ethanol, n-propanol, isopropanol, and butanol; ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, and n-octane; and alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane, and these can be used alone or in combination of two or more.

[0034] ((B) Layer Comprising a Water-Soluble Polymer) The gas barrier laminate of the present invention has a layer (B) containing a water-soluble polymer (B) (hereinafter, sometimes referred to as layer (B)). The layer (B) may be laminated so that at least a part of the layer (B) is in direct contact with the inorganic layer of the layer (A), and another layer such as layer (C) described below may be present between the layer (B) and the layer (A).

[0035] The water-soluble polymer contained in the (B) layer is not particularly limited as long as the effects of the present invention can be obtained. For example, one or more water-soluble polymers can be used, including vinyl alcohol polymers such as polyvinyl alcohol, ethylene-vinyl alcohol polymers, vinylpyrrolidone polymers, carboxyl group-containing resins such as (meth)acrylic acid polymers, salts of resins having carboxyl groups, polyvinyl butyral, starch, methyl cellulose, carboxymethyl cellulose, and sodium alginate. Among these, it is preferable to use one or more selected from vinyl alcohol polymers, ethylene-vinyl alcohol polymers, vinylpyrrolidone polymers, polyvinyl butyral, (meth)acrylic acid polymers, and ammonium salts of acrylic acid polymers, since these can provide suitable gas barrier properties.

[0036] The vinyl alcohol polymer may be a modified polyvinyl alcohol having a reactive functional group other than a hydroxyl group, such as an acetoacetyl group, a carboxyl group, an anionic carboxyl group, a sulfonic acid group, an anionic sulfonic acid group, etc. These may be used alone or in combination of two or more kinds.

[0037] Examples of vinyl alcohol polymers include hydrolyzates of homopolymers or copolymers of vinyl esters, and compounds obtained by reacting hydrolyzates of homopolymers or copolymers of vinyl esters with aldehydes or ketones to form acetals. Examples of vinyl alcohol polymers having reactive functional groups other than hydroxyl groups include hydrolyzates of copolymers of vinyl esters and monomers having reactive functional groups, and compounds in which the hydroxyl or acetyl groups of hydrolyzates of homopolymers or copolymers of vinyl esters are modified (denatured) by a known method using compounds having reactive functional groups.

[0038] Examples of vinyl esters include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, vinyl acetoacetate, etc., and one or more of these can be used in combination. It is preferable to use vinyl acetate.

[0039] Polymerizable compounds that can be copolymerized with vinyl esters include ethylene, propene, 1-butene, isobutylene, 1,3-butadiene, isopropenyl acetate, 2-propenyl acetate, styrene, α-methylstyrene, vinyl chloride, acrylonitrile, maleic anhydride, methyl acrylate, methyl methacrylate, N-vinyl-N-methylformamide, vinylacetamide, N-vinylformamide, N-(hydroxymethyl)-N-vinylformamide, hydroxyethyl acrylate, methyl vinyl ketone, diacetone acrylamide, and diacetone acrylamide. Examples of the acrylates include acrylate, diacetone methacrylamide, acrolein, formylstyrene, vinyl methyl ketone, vinyl ethyl ketone, vinyl isobutyl ketone, diacetone acrylate, diacetone methacrylate, acetonitrile acrylate, 2-hydroxypropyl acrylate acetoacetate, butanediol acrylate acetate, vinyl sulfonic acid, acrylamide tertiary butyl sulfonic acid, orthostyrene sulfonic acid, metastyrene sulfonic acid, parastyrene sulfonic acid, etc., and one or more of them can be used in combination. Among them, it is preferable to use ethylene, isopropenyl acetate, and 2-propenyl acetate.

[0040] When a vinyl ester and a polymerizable compound are used in combination, the amounts used can be appropriately adjusted. From the viewpoint of gas barrier properties, however, the amount of the polymerizable compound is preferably kept to 60 mol % or less, more preferably 25 mol % or less, of the total amount of the vinyl ester and the polymerizable compound.

[0041] The degree of polymerization of the vinyl ester polymer, which is a precursor of the vinyl alcohol polymer, is not particularly limited, but is, for example, 500 to 10,000, more preferably 800 to 6,000, and more preferably 1,000 to 3,000. This makes it possible to provide a coating agent with an excellent balance between gas barrier properties and coatability.

[0042] The vinyl alcohol polymer has a degree of saponification of preferably 90% or more, more preferably 95% or more, because it has excellent gas barrier properties. It may be 100%. The degree of saponification can be measured by FTIR using, for example, a Nicolet 5700 FTIR spectrometer controlled by OMNIC software.

[0043] When a vinyl alcohol polymer is acetalized, examples of the aldehyde used for the acetalization include aliphatic aldehydes such as formaldehyde, acetaldehyde, propylaldehyde, butylaldehyde, octylaldehyde, and dodecylaldehyde; alicyclic aldehydes such as cyclohexanecarbaldehyde; aromatic aldehydes such as benzaldehyde, naphthaldehyde, anthraldehyde, phenylacetaldehyde, tolualdehyde, dimethylbenzaldehyde, cuminaldehyde, and benzylaldehyde; unsaturated aldehydes such as cyclohexene aldehyde, dimethylcyclohexene aldehyde, and acrolein; aldehydes having a heterocycle such as furfural and 5-methylfurfural; hemiacetals such as glucose and glucosamine; and aldehydes having an amino group such as 4-aminobutyraldehyde. Examples of the ketone include aliphatic ketones such as 2-propanone, methyl ethyl ketone, 3-pentanone, and 2-hexanone, aliphatic alicyclic ketones such as cyclopentanone and cyclohexanone, and aromatic ketones such as acetophenone and benzophenone, etc. These can be used alone or in combination of two or more kinds.

[0044] As the acid catalyst used in the acetalization, conventionally known organic acids or inorganic acids such as acetic acid, paratoluenesulfonic acid, nitric acid, sulfuric acid, and hydrochloric acid can be used.

[0045] The vinyl alcohol polymer is preferably one obtained by acetalizing a precursor having a saponification degree of 95% or more.

[0046] Examples of the method for modifying the hydroxyl group or acetyl group of the hydrolyzate of the homopolymer or copolymer of vinyl ester include a method of directly reacting gaseous or liquid diketene, a method of adsorbing and storing an organic acid such as acetic acid in advance, and then reacting gaseous or liquid diketene with it under an inert gas atmosphere, or a method of spraying a mixture of an organic acid and diketene and reacting it, etc., by reacting diketene (reaction generation process), then washing and removing unreacted diketene with an alcohol having 1 to 3 carbon atoms (washing process), and then drying under a predetermined condition (drying process), and a method of reacting a hydrolyzate of the homopolymer or copolymer of vinyl ester with an acetoacetic ester to perform ester exchange, etc. This allows the introduction of an acetoacetyl group into the vinyl alcohol-based polymer.

[0047] In the resin having a carboxyl group (sometimes referred to as a carboxylic acid group) used in the present invention, the carboxyl group may include a carboxylic acid anhydride.

[0048] The resin having a carboxyl group is not particularly limited in terms of the resin skeleton, and any known resin can be used. Among them, a carboxyl group-containing vinyl resin is preferable.

[0049] (Carboxyl group-containing vinyl resin) The carboxyl group-containing vinyl resin may be, for example, a polymer of a polymerizable unsaturated monomer having a carboxyl group. Examples of the polymerizable unsaturated monomer having a carboxyl group include unsaturated carboxylic acids such as (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, crotonic acid, itaconic acid, maleic acid, and fumaric acid; monoesters (half esters) of various unsaturated dicarboxylic acids such as monomethyl itaconate, mono-n-butyl itaconate, monomethyl maleate, mono-n-butyl maleate, monomethyl fumarate, and mono-n-butyl fumarate with saturated monohydric alcohols; monovinyl esters of various saturated dicarboxylic acids such as monovinyl adipate and monovinyl succinate; addition reaction products of various anhydrides of saturated polycarboxylic acids such as succinic anhydride, glutaric anhydride, phthalic anhydride, and trimellitic anhydride with various hydroxyl group-containing vinyl monomers; and further, various monomers obtained by addition reaction of various carboxyl group-containing monomers as described above with lactones.

[0050] The resin having a carboxyl group used in the present invention may be a homopolymer of the above-mentioned polymerizable unsaturated monomer having a carboxyl group, or a copolymer using a plurality of polymerizable unsaturated monomers having a carboxyl group. Also, it may be a copolymer of a polymerizable unsaturated monomer having a carboxyl group and another monomer copolymerizable therewith.

[0051] Examples of monomers copolymerizable with the polymerizable unsaturated monomer having a carboxyl group include the following.

[0052] (1) (meth)acrylic acid esters having an alkyl group having 1 to 22 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, stearyl (meth)acrylate, octadecyl (meth)acrylate, and docosyl (meth)acrylate;

[0053] (2) (meth)acrylic acid esters having an alicyclic alkyl group, such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; (3) (meth)acrylic acid esters having an aromatic ring, such as benzoyloxyethyl (meth)acrylate, benzyl (meth)acrylate, phenylethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate;

[0054] (4) acrylic esters having a hydroxyalkyl group, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, lactone-modified hydroxyethyl (meth)acrylate, polyethylene glycol (meth)acrylate, and polypropylene glycol (meth)acrylate, etc.

[0055] (5) unsaturated dicarboxylic acid esters such as dimethyl fumarate, diethyl fumarate, dibutyl fumarate, dimethyl itaconate, dibutyl itaconate, methyl ethyl fumarate, methyl butyl fumarate, and methyl ethyl itaconate; (6) styrene derivatives such as styrene, α-methylstyrene, and chlorostyrene; (7) diene compounds such as butadiene, isoprene, piperylene, and dimethylbutadiene; (8) vinyl halides and vinylidene halides such as vinyl chloride and vinyl bromide; (9) unsaturated ketones such as methyl vinyl ketone and butyl vinyl ketone; (10) vinyl esters such as vinyl acetate and vinyl butyrate; (11) vinyl ethers such as methyl vinyl ether and butyl vinyl ether; (12) vinyl cyanides such as acrylonitrile, methacrylonitrile, and vinylidene cyanide; (13) acrylamide and its alkyd-substituted amides; (14) N-substituted maleimides such as N-phenylmaleimide and N-cyclohexylmaleimide;

[0056] (15) Fluorine-containing α-olefins such as vinyl fluoride, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, bromotrifluoroethylene, pentafluoropropylene, or hexafluoropropylene; or (per)fluoroalkyl perfluorovinyl ethers in which the (per)fluoroalkyl group has 1 to 18 carbon atoms, such as trifluoromethyl trifluorovinyl ether, pentafluoroethyl trifluorovinyl ether, or heptafluoropropyl trifluorovinyl ether; fluorine-containing ethylenically unsaturated monomers such as (per)fluoroalkyl (meth)acrylates in which the (per)fluoroalkyl group has 1 to 18 carbon atoms, such as 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, 1H,1H,2H,2H-heptadecafluorodecyl (meth)acrylate, or perfluoroethyloxyethyl (meth)acrylate;

[0057] (16) silyl group-containing (meth)acrylates such as γ-methacryloxypropyltrimethoxysilane, and (17) N,N-dialkylaminoalkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-diethylaminopropyl (meth)acrylate. These polymerizable unsaturated monomers may be used alone or in combination of two or more.

[0058] The resin having a carboxyl group can be obtained by polymerization (copolymerization) using a known and commonly used method, and the copolymerization form is not particularly limited. It can be produced by addition polymerization in the presence of a catalyst (polymerization initiator), and may be any of a random copolymer, a block copolymer, a graft copolymer, etc. Also, as the copolymerization method, known polymerization methods such as a bulk polymerization method, a solution polymerization method, a suspension polymerization method, and an emulsion polymerization method can be used.

[0059] (Acid value) The resin having a carboxyl group preferably has an acid value of 50 to 1000 mgKOH / g since the barrier performance is improved. The acid value is particularly preferably 80 to 900 mgKOH / g. If the acid value is 80 mgKOH / g or more, ionic bonding is sufficiently promoted and high barrier performance is obtained.

[0060] (Acid value measurement method) The acid value is the amount of potassium hydroxide (mg) required to neutralize the acid content in 1 g of sample. Specifically, a weighed sample is dissolved in a suitable solvent in which the sample dissolves, for example, a solvent with a volume ratio of toluene / methanol = 70 / 30, and several drops of a 1% phenolphthalein alcohol solution are dropped into the solution, and a 0.1 mol / L potassium hydroxide alcohol solution is dropped into the solution to confirm the discoloration point. The acid value can be measured by the following calculation formula.

[0061] Acid value measurement method-1 Acid value (mgKOH / g)=(V×F×5.61) / S V: Amount of 0.1 mol / L potassium hydroxide alcohol solution used (mL) F: Potency of 0.1 mol / L potassium hydroxide alcohol solution S: Amount of sample collected (g) 5.61: The amount of potassium hydroxide (mg) in 1 mL of 0.1 mol / L potassium hydroxide alcohol solution

[0062] If the sample is a resin solution, the resin acid value (mgKOH / g) can be calculated using the following formula.

[0063] Resin acid value (mgKOH / g) = Acid value of resin solution (mgKOH / g) / NV(%) x 100 NV: Non-volatile content (%)

[0064] In addition, when the solubility of the sample in an organic solvent is low and precipitation occurs, making the measurement difficult, the acid value can also be measured by the following method.

[0065] Acid value measurement method-2 The acid value (mgKOH / g-resin) is a value calculated by the following formula using an FT-IR (JASCO Corporation, FT-IR4200) and the coefficient (f) obtained from a calibration curve prepared using a chloroform solution of maleic anhydride, the absorbance (I) of the stretching peak (1780 cm-1) of the anhydride ring of maleic anhydride in a maleic anhydride-modified polyolefin solution, and the absorbance (II) of the stretching peak (1720 cm-1) of the carbonyl group of maleic acid. Acid value (mg KOH / g-regin) = [(absorbance (I) x (f) x 2 x molecular weight of potassium hydroxide x 1000 (mg) + absorbance (II) x (f) x molecular weight of potassium hydroxide x 1000 (mg)) / molecular weight of maleic anhydride] Molecular weight of maleic anhydride: 98.06, Molecular weight of potassium hydroxide: 56.11

[0066] (Molecular weight of resin having carboxyl group) In the present invention, the resin having a carboxyl group used preferably has a weight average molecular weight in the range of 1,000 to 10,000,000, more preferably in the range of 3,000 to 5,000,000, and even more preferably in the range of 5,000 to 1,000,000.

[0067] The salt of the resin having a carboxyl group may be any resin having a carboxyl group described above neutralized with a general base, and is preferably an ammonium salt neutralized with ammonium. Whether or not the resin has been neutralized can be determined by pH, and the pH of a 15% aqueous solution of the resin having a carboxyl group is preferably 7.0 to 9.0.

[0068] The ammonium used for neutralization is not particularly limited, but for example, a commonly available 30% aqueous ammonia solution can be used.

[0069] As the resin having a carboxyl group, polyacrylic acid, which is a homopolymer of (meth)acrylic acid, and ammonium salts of polyacrylic acid are preferable.

[0070] (Metal alkoxide and / or its hydrolysate) The (B) layer may contain a metal alkoxide and / or a hydrolysate thereof. The metal alkoxide and / or the hydrolysate thereof used is not particularly limited as long as the effects of the present invention can be obtained, but a metal alkoxide and / or a hydrolysate thereof having one or more metal species selected from silicon, aluminum, titanium, and zirconia as the metal species is preferable, and one or more metal species selected from silicon and aluminum as the metal species is more preferable in terms of improving gas barrier properties.

[0071] In these metal alkoxides and / or hydrolysates thereof, the hydroxyl group of the hydroxide of the above metal species is -OCH3, -OC2H5, -OC3H7, -OC n H 2n+1 The metal alkoxide and hydrolysate thereof may be one or more compounds selected from metal alkoxides substituted with an alkoxyl group represented by the formula (I) or (II), and hydrolysates thereof. As the metal alkoxide and hydrolysate thereof used in the present invention, alkoxysilanes such as tetraethoxysilane (TEOS), tetramethoxysilane, tetraproxisilane, tetrabutoxysilane, etc. can be used, and one or more metal alkoxides and / or hydrolysates thereof selected from tetraethoxysilane and tetramethoxysilane are particularly preferred because they provide good gas barrier properties.

[0072] The water-soluble polymer and the metal alkoxide and / or its hydrolysate are preferably mixed so that the solid content ratio is within the range of 70:30 to 15:85, more preferably 60:40 to 20:80, and most preferably 50:50 to 25:75.

[0073] (Polyvalent metal compounds) The (B) layer may contain a polyvalent metal compound. The polyvalent metal compound used is preferably a divalent metal compound. Examples of the divalent metal compound include zinc compounds, magnesium compounds, calcium compounds, manganese compounds, iron compounds, cobalt compounds, nickel compounds, and copper compounds, and zinc compounds, magnesium compounds, and calcium compounds are particularly preferred. These metal compounds may be used alone or in combination of two or more.

[0074] The divalent metal compound is preferably an oxide, hydroxide or carbonate of a divalent metal, and may be a mixture of these. Specific examples of the divalent metal compound include zinc oxide, magnesium oxide, and calcium oxide, and particularly preferably zinc oxide and magnesium oxide.

[0075] The divalent metal compound is preferably in the form of particles. More preferably, it is fine particles having an average particle size of 10 nm or more and 500 nm or less. Particularly preferably, it is fine particles having an average particle size of 20 nm to 300 nm. The average particle size here can be measured using a dynamic light scattering type particle size distribution measuring device, for example, LB-500 (manufactured by Horiba, Ltd.).

[0076] The polyvalent metal compound is preferably used together with the ammonium salt of the resin having a carboxyl group, and is preferably contained in an amount of 0.1 to 2.3 chemical equivalents relative to the carboxyl group. In particular, the content is preferably 0.2 to 1.5 chemical equivalents, and more preferably 0.3 to 1.2 chemical equivalents. If the content is less than 0.1 equivalents, crosslinking of the resin having a carboxyl group by the metal ion of the polyvalent metal compound is insufficient, resulting in poor gas barrier properties. If the content is more than 2.3 equivalents, the liquid stability of the coating material is poor.

[0077] In the present invention, the chemical equivalent is calculated and referred to as follows. For example, the molecular weight of a unit of ammonium polyacrylate, a resin with carboxyl groups, is 89. Normally, for every two molecules of ammonium polyacrylate (twice the molecular weight of 89), one molecule of zinc oxide (molecular weight 81.4), a polyvalent metal compound, contributes to the reaction and forms a salt. A formulation in which the weight of ammonium polyacrylate:weight of zinc oxide is 178 / 81.4=100 / 45.7 is said to contain 1 equivalent of zinc oxide.

[0078] (Method of manufacturing layer (B)) The (B) layer can be obtained by preparing a coating material in which the water-soluble polymer and, if necessary, a metal alkoxide and / or its hydrolysate or a polyvalent metal compound are dissolved or dispersed in an aqueous solvent, applying the coating material onto the inorganic layer of the (A) layer, and drying and solidifying the coating material.

[0079] The aqueous solvent may be water or a water-soluble organic solvent such as methanol, ethanol, isopropanol, or 1-propanol, and is preferably a mixture of water and the water-soluble organic solvent. Dissolution or dispersion can be carried out by a known method.

[0080] The method for applying the prepared coating material is not particularly limited, and any known and commonly used coating method can be used, such as spraying, spin coating, dipping, roll coating, blade coating, doctor roll, doctor blade, curtain coating, slit coating, screen printing, inkjet, and dispensing, and in particular, roll coating using a gravure coater is preferred because it allows a good coating film to be formed.

[0081] The coating amount of the mixed coating material is not particularly limited as long as the effects of the present invention can be obtained, but is preferably 0.05 to 1.0 g / m 2 It is preferable to coat the coating material in an amount of 0.1 to 0.5 g / m. 2 It is preferable to coat the coating material in an amount of 0.2 to 0.4 g / m because a good coating film is formed. 2It is particularly preferred that the coating amount is 100%.

[0082] It is preferable to provide a drying step after coating of the (B) layer. The drying step may be drying at room temperature or forced drying using an oven or the like, under reduced pressure, or by blowing air.

[0083] Layer (B) may contain additives other than those mentioned above, such as a silane coupling agent or a wetting agent such as a surfactant, within the range in which the effects of the present invention can be obtained.

[0084] (Method of manufacturing gas barrier laminate) The gas barrier laminate of the present invention can be obtained by carrying out, in order, step 1, a corona treatment, ozone treatment, plasma treatment, ultraviolet irradiation treatment, or excimer UV treatment on the inorganic layer of layer (A) made of a substrate having an inorganic layer formed on at least one surface thereof, and step 2, providing layer (B) containing a water-soluble polymer on layer (A).

[0085] Layer (A), which is made of a substrate having an inorganic layer formed on at least one surface thereof, can be obtained by forming a layer of an inorganic material such as aluminum oxide, silicon oxide, aluminum, zinc oxide, or magnesium oxide on the substrate such as an olefin by a method such as vapor deposition or sputtering, as described above.

[0086] The corona treatment, ozone treatment, plasma treatment, ultraviolet irradiation treatment, or excimer UV treatment carried out on the inorganic layer of the layer (A) may also be carried out by the method described above.

[0087] Step 2 of providing a (B) layer containing a water-soluble polymer on the (A) layer that has been subjected to the above treatment can be carried out by the above-mentioned method for producing the (B) layer.

[0088] (Other layers) In the gas barrier laminate of the present invention, in addition to the (A) layer and the (B) layer, various combinations of layers such as a (C) layer having 50 mass % or more of an organometallic compound having a Group 4 metal species (C), a (D) layer having a polyvalent metal compound, a resin layer which is a base material used in the (A) layer but has no inorganic layer formed thereon or a layer made of a material other than the above (second base material layer), a printed layer, a functional coating layer, an adhesive layer, etc. may be used.

[0089] ((C) Layer containing 50% by mass or more of an organometallic compound having a Group 4 element as a metal species) In the present invention, a layer containing 50 mass % or more of an organometallic compound having a Group 4 element as a metal species (hereinafter, sometimes referred to as Layer (C)) may be provided between Layer (A) and Layer (B) so as to be in contact with the surface of Layer (A) on which the inorganic layer is formed.

[0090] In the organometallic compound used in the present invention, which contains a Group 4 element as the metal species, specific examples of the Group 4 element metal species include titanium, zirconium, hafnium, and rutherfordium. Among these, titanium or zirconium is preferable.

[0091] Examples of organometallic compounds containing these Group 4 elements as metal species include metal alkoxides and / or their oligomers and / or their hydrolysates, metal acylates, metal complexes, coupling agents, etc. These organometallic compounds may be used alone or in combination of two or more.

[0092] As for the metal alkoxide and / or their oligomers and / or their hydrolysates, the hydroxyl group of the hydroxide of the metal species is -OC3H7, -OC4H9, -OCH2CH(C2H5)C4H9, -OCH(CH3)2, -OC n H 2n+1The metal alkoxide may be one or more compounds selected from metal alkoxides substituted with alkoxyl groups represented by the formula (I) and hydrolysates thereof. Examples of the metal alkoxides and hydrolysates thereof used in the present invention include tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetraoctyl titanate, butyl titanate oligomer, tetraisopropyl zirconate, tetra-n-butyl zirconate, etc. Particularly preferred is one or more metal alkoxides selected from tetra-normal-butyl titanate and tetra-normal-butyl zirconate and / or hydrolysates thereof.

[0093] As the metal acylate, specifically, for example, titanium isostearate, zirconium isoctylate, zirconium stearate, etc. can be used.

[0094] Metal complexes are sometimes referred to as chelating agents. Specific examples include titanium tetraalkylates such as titanium tetrapropylate and titanium tetrabutylate, titanium alkylacetoacetates such as titanium bis(acetylacetate)dipropylate, and zirconium tetraalkylates such as zirconium tetrabutylate.

[0095] Coupling agents include titanium coupling agents such as isopropyl triisostearoyl titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl) bis(ditridecyl) phosphite titanate, bis(dioctyl pyrophosphate) oxyacetate titanate, bis(dioctyl pyrophosphate) ethylene titanate, etc. Zirconium coupling agents include zirconium acetate, ammonium zirconium carbonate, zirconium fluoride, etc.

[0096] In the present invention, the lower limit of the content of the organometallic compound having a Group 4 metal species relative to the total solid content of Layer (C) is preferably 50 mass%, 55 mass%, or 60 mass%, and the upper limit of the content is preferably 100% relative to the total solid content.

[0097] The (C) layer can be obtained, for example, by a coating method. The coating method is not particularly limited, and any known and commonly used coating method can be used. Examples of the coating method include spraying, spin coating, dip coating, roll coating, blade coating, doctor roll, doctor blade, curtain coating, slit coating, screen printing, inkjet, and dispense methods.

[0098] When the (C) layer is obtained by a coating method, a solvent can be used to improve the coating suitability. The solvent is preferably an organic solvent, and examples of the solvent include alcohol-based organic solvents such as ethanol, n-propanol, isopropyl alcohol, butanol, ketone-based organic solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, n-octane, cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, and the like, and these can be used alone or in combination of two or more.

[0099] The coating amount of the organometallic compound having a Group 4 element as a metal species is not particularly limited as long as the effects of the present invention can be obtained, but is preferably 0.001 to 0.5 g / m in terms of solid content. 2 It is preferable to coat the film in an amount of 0.003 to 0.2 g / m because good barrier properties can be obtained. 2 It is particularly preferred that the coating amount is 100%.

[0100] It is preferable to provide a drying step after coating of Layer C. The drying step may be room temperature drying or forced drying using an oven or the like, reduced pressure, or air blowing.

[0101] As described above, Layer C in the present invention contains an organometallic compound having a Group 4 element as the metal species in an amount of 50 mass % or more relative to the total solid content. Additives such as a stabilizer, a resin serving as a binder component, a coupling agent, a plasticizer, a dispersant, a surfactant, a stabilizer, a thickener, an antifoaming agent, a wetting agent, a hardener, an antiblocking agent, a lubricant, a preservative, and an inorganic filler may be blended within a range in which the effects of the present invention can be obtained.

[0102] In particular, when layer (C) is obtained by a coating method using a metal alkoxide and / or an oligomer thereof, and / or a hydrolysate thereof as the organometallic compound, it is preferred that the layer contains a stabilizer. As the stabilizer, acetylacetone, dehydroacetic acid, benzoylacetone, ethyl acetoacetate, diacetyl and other diketones, carboxylic acids such as acetic acid, hydroxycarboxylic acids such as citric acid, malic acid, tartaric acid, mandelic acid, lactic acid, glycolic acid, hydroxyisobutyric acid, hydroxyacetone, hydroxycarbonyls such as acetoin, cellosolves such as methoxyethanol, dimethoxyethane, glycols such as ethylene glycol, substituted glycol, pentaethylene glycol, hydrazones such as acetolhydrazone, acetoinhydrazone, imines such as diethanolamine, monoketones such as acetone, and the like can be used, and among them, it is preferable to select from acetylacetone, benzoylacetone, citric acid, malic acid, mandelic acid, and acetone.In addition, acetone also functions as a solvent as mentioned above.

[0103] The stabilizer is contained in an amount of preferably 5 to 45% and most preferably 7 to 40% based on the solid content of Layer (C).

[0104] In addition, by containing a resin that serves as a binder component, the coating suitability can be improved. Examples of binder resins include polyvinyl acetal resins such as polyvinyl butyral resins and polyvinyl acetacetal resins, acrylic resins, polyester resins, styrene resins, styrene-maleic acid resins, maleic acid resins, polyamide resins, polyurethane resins, vinyl chloride-vinyl acetate copolymer resins, vinyl chloride-acrylic copolymer resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, polyvinyl chloride resins, chlorinated polypropylene resins, cellulose-based resins, epoxy resins, alkyd resins, rosin-based resins, rosin-modified maleic acid resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyrals, and petroleum resins.

[0105] The binder resin is contained in an amount of preferably 0% to 40% and most preferably 0% to 35% based on the solid content of Layer C.

[0106] The coupling agent may be any of the known and commonly used ones, such as a silane coupling agent, a titanium coupling agent, a zirconium coupling agent, and an aluminum coupling agent.

[0107] The silane coupling agent may be any known or commonly used one, and examples thereof include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acryloyl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.

[0108] Examples of the aluminum coupling agent include acetoalkoxy aluminum diisopropylate, aluminum diisopropoxymonoethyl acetoacetate, aluminum trisethyl acetoacetate, and aluminum trisacetylacetonate.

[0109] Examples of the silane compound include alkoxysilane, silazane, and siloxane. Examples of the alkoxysilane include methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, and trifluoropropyltrimethoxysilane. Examples of the silazane include hexamethyldisilazane. Examples of the siloxane include hydrolyzable group-containing siloxane.

[0110] The coupling agent is contained in an amount of preferably 0% to 40% and most preferably 0% to 35% based on the solid content of the layer (C).

[0111] In the present invention, when the (C) layer is present, the (C) layer and the (B) layer are preferably combined to form a strong film by a polycondensation reaction using a sol-gel method. Various catalysts and solvents may be added as necessary, and drying by heating may be performed.

[0112] In the present invention, when the (C) layer is present, the (B) layer is preferably provided so as to be in contact with the (C) layer. There is no particular limitation on the method for providing the (C) layer on the (A) layer by coating, and then the (B) layer is continuously provided by coating, or the (C) layer is provided on the (A) layer by coating, and then wound up once, and then unwound, and then the (B) layer is provided on the (C) layer by coating, and any other commonly used method may be used.

[0113] (Layer (D) having polyvalent metal compound) The gas barrier film of the present invention may further include a layer (D) containing a polyvalent metal compound adjacent to the layer (B) containing the water-soluble polymer, where "adjacent" means that there is at least a portion where the layer (B) and the layer (D) are in direct contact with each other.

[0114] The polyvalent metal compound contained in the (D) layer is a divalent or higher metal compound, which is mixed with a resin or the like to form the (D) layer. Examples of such polyvalent metal compounds include zinc compounds, magnesium compounds, calcium compounds, manganese compounds, iron compounds, cobalt compounds, nickel compounds, and copper compounds, and zinc compounds, magnesium compounds, and calcium compounds are particularly preferred. These metal compounds may be used alone or in combination of two or more.

[0115] The polyvalent metal compound that may be used in the present invention is preferably an oxide, hydroxide, or carbonate of a divalent metal, or may be a mixture of these. As the divalent metal compound, zinc oxide, magnesium oxide, and calcium oxide are preferred, and zinc oxide and magnesium oxide are particularly preferred.

[0116] The polyvalent metal compound is preferably in the form of particles. More preferably, it is fine particles having an average particle size of 10 nm or more and 500 nm or less. Particularly preferably, it is fine particles having an average particle size of 20 nm to 300 nm. The average particle size here is measured using a dynamic light scattering type particle size distribution measuring device, for example, LB-500 (manufactured by Horiba, Ltd.).

[0117] The polyvalent metal compound is preferably contained in the layer (D) containing a polyvalent metal compound in a range of 40 to 90 parts by mass, and particularly preferably in a range of 60 to 80 parts by mass, since this improves the gas barrier properties.

[0118] In addition to the polyvalent metal compound, a resin is added to the (D) layer containing the polyvalent metal compound in order to stably coat the polyvalent metal compound.Specific examples of the resin include cellulose resins, ethyl cellulose resins, carboxymethyl cellulose resins, polyester resins, epoxy resins, carboxyl group-containing resins, salts of resins having carboxyl groups, methacrylic resins, polyamide resins, polyether polyurethane polyol resins, polyester polyol resins and polyurethane polyol resins, styrene resins, styrene-maleic acid resins, vinyl chloride-vinyl acetate copolymer resins, vinyl chloride-acrylic copolymer resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, polyvinyl chloride resins, chlorinated polypropylene resins, alkyd resins, rosin resins, rosin-modified maleic acid resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyral, and petroleum resins.These resins may be used alone or in combination.Of these, ethyl cellulose resins, polyether polyurethane polyol resins, polyester polyol resins, polyurethane polyol resins, acrylic resins, maleic acid resins, and salts of acrylic resins are preferred.

[0119] The resin is preferably contained in the resin layer (B) containing a polyvalent metal compound in an amount of 5 to 70 parts by mass, and a range of 10 to 50 parts by mass is particularly preferred because this range improves the coatability of the resin layer (B).

[0120] In the present invention, when the (D) layer is present, the (B) layer is preferably provided so as to be in contact with the (D) layer. There is no particular limitation on the method for providing the (B) layer on the (A) layer by coating, and then the (D) layer is continuously provided by coating, or the (B) layer is provided on the (A) layer by coating, and then wound up once, and then unwound, and then the (D) layer is provided on the (B) layer by coating, and any other commonly used method may be used.

[0121]

[0051] Specific embodiments of the layer structure of the gas barrier laminate of the present invention are shown below, but the present invention is not limited to these, and any laminate comprising a combination of a second base material layer, a printed layer, a functional coating layer, an adhesive layer, and an ink layer, as described below, may be used, so long as the effects of the present invention are not impaired. Layer (A) (substrate / inorganic layer) / Layer (B) / adhesive layer / second substrate layer Layer (A) (substrate / inorganic layer) / Layer (B) / Layer (D) / Adhesive layer / Second substrate layer Layer (A) (substrate / inorganic layer) / Layer (C) / Layer (B) / Adhesive layer / Second substrate layer Layer (A) (substrate / inorganic layer) / Layer (C) / Layer (B) / Layer (D) / Adhesive layer / Second substrate layer Layer (A) (substrate / inorganic layer) / Layer (B) / Layer (C) / Adhesive layer / Second substrate layer Layer (A) (substrate / inorganic layer) / Layer (D) / Layer (B) / Adhesive layer / Second substrate layer Layer (A) (substrate / inorganic layer) / Layer (D) / Layer (B) / Layer (C) / Adhesive layer / Second substrate layer In such an embodiment, when a printed layer or a functional coating layer is provided, it can be provided on the surface of Layer (A) opposite the inorganic layer, on the surface of the inorganic layer of Layer (A), or on the surface of the adhesive layer opposite the second base material layer.

[0122] Second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (B) layer Second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (B) layer / (D) layer Second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (C) layer / (B) layer Second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (C) layer / (B) layer / (D) layer Second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (B) layer / (C) layer Second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (D) layer / (B) layer Second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (D) layer / (B) layer / (C) layer In such an embodiment, when a printed layer or a coating layer having functionality is provided, it can be provided either on the side opposite to the inorganic layer of Layer (A) or on the side of the inorganic layer of Layer (A).

[0123] Second substrate layer / adhesive layer / Layer (A) (substrate / inorganic layer) / Layer (B) / adhesive layer / second substrate layer second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (B) layer / (D) layer / adhesive layer / second substrate layer second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (C) layer / (B) layer / adhesive layer / second substrate layer second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (C) layer / (B) layer / (D) layer / adhesive layer / second substrate layer second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (B) layer / (C) layer / adhesive layer / second substrate layer second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (D) layer / (B) layer / adhesive layer / second substrate layer second substrate layer / adhesive layer / (A) layer (substrate / inorganic layer) / (D) layer / (B) layer / (C) layer / adhesive layer / second substrate layer In such an embodiment, when a printed layer or a functional coating layer is provided, it can be provided on the surface of Layer (A) opposite the inorganic layer, on the surface of the inorganic layer of Layer (A), or on the surface of the adhesive layer opposite the second base material layer.

[0124] (Second base layer) In the present invention, the substrate layer used in the layer (A) on which no inorganic layer is formed includes, as described above for the layer (A), olefin resins such as polyethylene (PE), polypropylene (PP), cyclic olefin polymer (COP), and cyclic olefin copolymer (COC), polyester, acrylic, polycarbonate, cellulose ester, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), nylon (NY), and materials containing biomass-derived components. In particular, any film made of a thermoplastic resin mainly composed of an olefin resin can be used without any particular limitation. Specific examples of olefin resins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene, polypropylene, ethylene-propylene copolymers, α-olefin polymers, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ethylene-acrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-ethyl acrylate copolymers, cyclic olefin resins, ionomer resins, and polymethylpentene; and modified olefin resins obtained by modifying olefin resins with acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, and other unsaturated carboxylic acids. Among these, olefin resins such as polyethylene (PE), polypropylene (PP), cyclic olefin polymers (COP), and cyclic olefin copolymers (COC) are preferably used because the effects of the present invention are significantly obtained, and polyethylene (PE) and polypropylene (PP) are the most preferred.

[0125] Examples of film names include polyethylene terephthalate (PET) film, polystyrene film, polyamide film, polyacrylonitrile film, polyethylene film (LLDPE: low density polyethylene film, HDPE: high density polyethylene film, MDOPE: uniaxially oriented polyethylene film, OPE: biaxially oriented polyethylene film), polyolefin film such as polypropylene film (CPP: non-oriented polypropylene film, OPP: biaxially oriented polypropylene film), polyvinyl alcohol film, ethylene-vinyl alcohol copolymer film, etc., and also biomass films formed from materials containing biomass-derived components are preferably used for food packaging. Biomass films are sold by various companies, and for example, sheets such as those listed in the list of biomass certified products listed in the Japan Organic Resources Association can be used.

[0126] The substrate may be, for example, wood, metal, metal oxide, a resin film other than the resin shown in the layer (A), paper, silicon or modified silicon, or a substrate obtained by bonding different materials. The shape of the substrate is not particularly limited, and may be any shape according to the purpose, such as a flat plate, a sheet, or a three-dimensional shape having a curvature on the entire surface or part. There is also no limit to the hardness, thickness, etc. of the substrate. When the laminate according to the present invention is used as a packaging material, paper, plastic, metal, metal oxide, etc. may be used as the substrate.

[0127] (Printing layer) From the viewpoint of recycling, it is preferable that the layer structure is as simple as possible, but from the viewpoint of distribution of the packaging material, printing is often required to display the contents of the packaging material or the description or name of the product. Liquid inks such as gravure printing inks and flexographic printing inks are often used as printing inks for this purpose.

[0128] The printed layer is a layer on which characters, figures, symbols, and other desired patterns are printed using liquid ink or the like. The laminate may be provided at any position. In this specification, liquid ink is a general term for solvent-based ink used in gravure printing or flexographic printing. It may contain a resin, a colorant, and a solvent as essential components, or it may be a so-called clear ink that contains a resin and a solvent but does not substantially contain a colorant.

[0129] The resin used in the liquid ink is not particularly limited, and examples thereof include acrylic resin, polyester resin, styrene resin, styrene-maleic acid resin, maleic acid resin, polyamide resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-acrylic copolymer resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, polyvinyl chloride resin, chlorinated polypropylene resin, cellulose-based resin, epoxy resin, alkyd resin, rosin-based resin, rosin-modified maleic acid resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, petroleum resin, etc., and one or more of them can be used in combination. Preferably, at least one or two or more selected from polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, and cellulose-based resin are used.

[0130] Colorants used in liquid inks include inorganic pigments such as titanium oxide, red iron oxide, antimony red, cadmium red, cadmium yellow, cobalt blue, Prussian blue, ultramarine, carbon black, and graphite; organic pigments such as soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments; and extender pigments such as calcium carbonate, kaolin clay, barium sulfate, aluminum hydroxide, and talc.

[0131] The organic solvent used in the liquid ink preferably does not contain an aromatic hydrocarbon-based organic solvent. More specifically, examples of the organic solvent include alcohol-based organic solvents such as methanol, ethanol, n-propanol, isopropyl alcohol, and butanol, ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate, aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, and n-octane, and alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane, and these may be used alone or in combination of two or more.

[0132] (Functional coating layer) Examples of functional coating layers include coating agents containing various additives. Examples of additives include modifiers, coupling agents, silane compounds, phosphoric acid compounds, organic fillers, inorganic fillers, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, etc.), plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, crystal nucleating agents, oxygen scavengers (compounds having oxygen scavenging function), tackifiers, etc. These various additives may be used alone or in combination of two or more.

[0133] The modifier may be any known or commonly used one, and for example, various compounds such as diols, amine compounds, carbodiimides, and isocyanates may be added.

[0134] The coupling agent may be any of the known and commonly used ones, such as a silane coupling agent, a titanium coupling agent, a zirconium coupling agent, and an aluminum coupling agent.

[0135] The silane coupling agent may be any known or commonly used one, and examples thereof include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acryloyl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.

[0136] Examples of titanium coupling agents include isopropyl triisostearoyl titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, and bis(dioctyl pyrophosphate)ethylene titanate.

[0137] Examples of zirconium coupling agents include zirconium acetate, ammonium zirconium carbonate, and zirconium fluoride.

[0138] Examples of the aluminum coupling agent include acetoalkoxy aluminum diisopropylate, aluminum diisopropoxy monoethyl acetoacetate, aluminum tris ethyl acetoacetate, and aluminum tris acetyl acetonate.

[0139] Examples of the silane compound include alkoxysilane, silazane, and siloxane. Examples of the alkoxysilane include methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, and trifluoropropyltrimethoxysilane. Examples of the silazane include hexamethyldisilazane. Examples of the siloxane include hydrolyzable group-containing siloxane.

[0140] Among the additives, inorganic fillers include inorganic substances such as metals, metal oxides, resins, and minerals, and composites thereof. Specific examples of inorganic fillers include silica, alumina, titanium, zirconia, copper, iron, silver, mica, talc, aluminum flakes, glass flakes, clay minerals, and the like.

[0141] Examples of compounds having an oxygen scavenging function include low molecular weight organic compounds that react with oxygen, such as hindered phenol compounds, vitamin C, vitamin E, organic phosphorus compounds, gallic acid, and pyrogallol, and transition metal compounds, such as cobalt, manganese, nickel, iron, and copper.

[0142] Examples of tackifiers include xylene resin, terpene resin, phenol resin, rosin resin, etc. Addition of a tackifier can improve adhesion to various substrates immediately after application. The amount of tackifier added is preferably 0.01 to 5 parts by mass with respect to 100 parts by mass of the total amount of the resin composition.

[0143] (Adhesive layer) The adhesive layer may be an adhesive that can be used in a general-purpose lamination method for laminating the gas barrier laminate of the present invention, particularly with a second substrate, etc. Examples of the lamination method include dry lamination, wet lamination, non-solvent lamination, and extrusion lamination. The adhesive used in the dry lamination may be, for example, a one-component or two-component curing or non-curing type vinyl, (meth)acrylic, polyamide, polyester, polyether, polyurethane, epoxy, rubber, or other solvent, water-based, or emulsion-type adhesive. A two-component curing adhesive of polyol and isocyanate compound may be used. The lamination adhesive may be applied by, for example, a direct gravure roll coating method, a gravure offset roll coating method, a kiss coating method, a reverse roll coating method, a Fontaine method, a transfer roll coating method, or other methods.

[0144] Also, various adhesives can be used, and it is preferable to use a pressure-sensitive adhesive. Examples of the pressure-sensitive adhesive include rubber-based adhesives obtained by dissolving polyisobutylene rubber, butyl rubber, or a mixture thereof in an organic solvent such as benzene, toluene, xylene, or hexane, or those obtained by blending a tackifier such as abiethylene acid rosin ester, terpene-phenol copolymer, or terpene-indene copolymer with these rubber-based adhesives, or acrylic-based adhesives obtained by dissolving an acrylic copolymer having a glass transition point of -20°C or less, such as 2-ethylhexyl acrylate-n-butyl acrylate copolymer or 2-ethylhexyl acrylate-ethyl acrylate-methyl methacrylate copolymer, in an organic solvent.

[0145] (Types of gas components that can be blocked from permeating) The gas that the gas barrier laminate of the present invention can block is mainly oxygen, but other examples include inert gases such as carbon dioxide, nitrogen, and argon, alcohol components such as methanol, ethanol, and propanol, phenols such as phenol and cresol, and aroma components made of low molecular weight compounds, for example, the smells of soy sauce, sauce, miso, limonene, menthol, methyl salicylate, coffee, cocoa, etc.

[0146] (packaging material) The gas barrier laminate of the present invention can be used as a multi-layer packaging material for protecting foods, medicines, etc. When used as a multi-layer packaging material, the layer structure can be changed depending on the contents, the environment of use, and the form of use. In addition, the package of the present invention may be appropriately provided with an easy-opening treatment or a resealing means.

[0147] Contents to be filled into the packaging material of the present invention include, for example, foods such as rice crackers, bean snacks, nuts, biscuits, cookies, wafers, marshmallows, pies, semi-dried cakes, candies, snacks, and other confectioneries; bread, snack noodles, instant noodles, dried noodles, pasta, aseptically packaged cooked rice, porridge, porridge, packaged rice cakes, cereal foods, and other staple foods; pickles, boiled beans, natto, miso, frozen tofu, tofu, nametake mushrooms, konjac, wild vegetable products, jams, peanut cream, salads, frozen vegetables, potato products, and other agricultural processed products; livestock products such as ham, bacon, sausages, chicken products, and corned beef; and fish. These include meat ham and sausages, fish paste products, fishery products such as kamaboko, nori seaweed, tsukudani (food boiled in soy sauce), dried bonito flakes, shiokara (salted fish), smoked salmon, and spicy cod roe, fruit pulp such as peaches, mandarin oranges, pineapples, apples, pears, and cherries, vegetables such as corn, asparagus, mushrooms, onions, carrots, radishes, and potatoes, prepared foods such as hamburger steaks, meatballs, seafood fries, frozen and chilled prepared dishes including gyoza (dumplings) and croquettes, dairy products such as butter, margarine, cheese, cream, instant creamy powder, and infant formula, liquid seasonings, retort curry, and pet food.

[0148] In addition, the composition can be used as a packaging material for various non-food items, such as tobacco, disposable hand warmers, medicines such as infusion packs, liquid laundry detergent, liquid kitchen detergent, liquid bath detergent, liquid bath soap, liquid shampoo, liquid conditioner, cosmetics such as lotion and milky lotion, vacuum insulation materials, batteries, etc. EXAMPLES

[0149] The present invention will be described in more detail below with reference to specific synthesis examples and examples, but the present invention is not limited to these examples. In the following examples, "parts" and "%" respectively represent "parts by mass" and "% by mass" unless otherwise specified.

[0150] (Measurement and evaluation methods) (Evaluation item 1: static contact angle) A 1.5 μL water droplet was dropped onto the surface of Layer (A) on which the inorganic layer was formed, and the static contact angle of the water droplet was measured at 25° C. using a contact angle meter (DMo-701). The unit of the static contact angle is degrees.

[0151] (Evaluation item 2: Surface free energy) The static contact angles of water and diiodomethane were measured in the same manner as described above, and the surface free energy was calculated using the Owens-Wendt-Kaelble method. The unit of surface free energy is mN / m.

[0152] (Evaluation item 3: Adhesion) A piece of Scotch tape (Nichiban, 12 mm width) was applied onto layer (B) of the prepared gas barrier laminate, and the appearance of the coating film when it was quickly peeled off was visually judged into the following three stages. (Evaluation Criteria) ◯: 70% or more of the printed film remained on the film. △: 30% to less than 70% of the printed film remained on the film. ×: Less than 30% of the printed film remained.

[0153] (Evaluation item 4: Laminate strength) The prepared packaging material was cut into 15 mm widths in a direction parallel to the direction in which the adhesive was applied. Next, the end of the long axis of the packaging material (the end cut into 15 mm widths) was peeled between a biaxially oriented polypropylene film (hereinafter sometimes referred to as OPP film) and a non-oriented polypropylene film (hereinafter sometimes referred to as CPP film). The two peeled layers were fixed to an "Autograph AGS-X" manufactured by Shimadzu Corporation, and peeled by a T-type peeling method with an atmospheric temperature of 25°C and a peeling speed of 300 mm / min to measure the tensile strength. The tensile strength measured here was taken as the laminate strength of the laminate of each Example and Comparative Example. The unit of adhesive strength is N / 15 mm.

[0154] (Evaluation item 5: Gas barrier properties (oxygen permeability)) The oxygen permeability was measured in accordance with JIS-K7126-2:2006 "Plastic films and sheets - Gas permeability test method - Part 2: Constant pressure method" using a Mocon oxygen permeability measuring device OX-TRAN2 / 21, under an atmosphere of temperature 23°C and humidity 0% RH, and under an atmosphere of temperature 23°C and humidity 90% RH. RH stands for relative humidity. The unit of oxygen permeability is cc / day·atm·m. 2 It is.

[0155] (Preparation of layer (A)) An anchor coating solution obtained by mixing an acrylic coating agent (GAC-013S, DIC Corporation) and a polyisocyanate curing agent (KR-90, DIC Corporation) in a mixing ratio of 5:1 was applied to a biaxially oriented polypropylene film (OPP film FOR, Futamura Chemical Co., Ltd., thickness 20 μm) by gravure coating so that the dry film thickness was about 0.05 μm, and dried to obtain an anchor coating layer. Then, in a vacuum deposition device using an electron beam heating method, metallic aluminum was deposited and oxygen gas was introduced. In this way, an (A) layer was formed having an anchor coating layer on the OPP film and an aluminum oxide deposition layer, which is an inorganic layer, having a thickness of 20 nm on the anchor coating layer.

[0156] (Corona treatment) The surface of the inorganic layer of Layer (A) was subjected to corona treatment by adjusting the output and speed to achieve a predetermined irradiation amount using a corona discharge treatment machine manufactured by Kasuga Electric Co., Ltd. The irradiation amount is as shown in the table below.

[0157] (Ozone treatment) The surface of the inorganic layer (A) was subjected to ozone cleaning treatment for a predetermined time using a UV-ozone cleaning device (OC-250315 / 6X-D+A) manufactured by Iwasaki Electric Co., Ltd. The time is as shown in the table below.

[0158] (Plasma treatment) The surface of the inorganic layer of layer (A) was subjected to plasma treatment for a specified time using a multipurpose plasma surface treatment device (POEM) manufactured by Shinko Seiki Co., Ltd., at normal pressure, oxygen flow rate of 100 ml / min, power of 400 W, and distance between the light source and layer (A) of 10 mm. The time is as shown in the table below.

[0159] (Preparation of coating solution (b-1) for (B layer)) Polyvinyl alcohol (PVA) (PVA60-98, Kuraray Co., Ltd., fully saponified PVA) was dissolved in a mixed solvent of water / isopropyl alcohol (IPA) = 98 / 2 (mass ratio) so that the solid content concentration was 5%, to prepare a PVA solution. Next, 0.1N hydrochloric acid was added to tetraethoxysilane (Si(OC2H5)4, hereinafter referred to as "TEOS"; KBE-04, Shin-Etsu Chemical Co., Ltd.), and the mixture was stirred for 30 minutes to hydrolyze the mixture to prepare a TEOS hydrolysis solution with a solid content of 3% (SiO2 equivalent). The PVA solution and the TEOS hydrolysis solution were mixed so that the solid content mass ratio of PVA / TEOS (SiO2 equivalent) was 30 / 70, to prepare a coating liquid (b-1).

[0160] (Preparation of coating solution (b-2) for (B layer)) Polyacrylic acid (PAA) (A-10H, Toagosei Co., Ltd.) was diluted with water to a solid content of 5% to prepare a PAA solution. Next, 0.1N hydrochloric acid was added to TEOS, and the mixture was stirred for 30 minutes to hydrolyze the solution, preparing a TEOS hydrolysis solution with a solid content of 3% (SiO2 equivalent). The PAA solution and the TEOS hydrolysis solution were mixed to a solid content mass ratio of PAA / TEOS (SiO2 equivalent) of 30 / 70 to prepare a coating solution (b-2).

[0161] (Preparation of coating solution (b-3) for (B layer)) Modified polyvinyl alcohol (modified PVA) (25-88KL, Kuraray Co., Ltd.) was dissolved in a mixed solvent of water / isopropyl alcohol (IPA) = 98 / 2 (mass ratio) so that the solid content concentration was 5%, to prepare a modified PVA solution. Next, 0.1N hydrochloric acid was added to TEOS, and the mixture was stirred for 30 minutes to hydrolyze the mixture, to prepare a TEOS hydrolysis solution with a solid content of 3% (SiO2 equivalent). The modified PVA solution and the TEOS hydrolysis solution were mixed so that the solid content mass ratio of modified PVA / TEOS (SiO2 equivalent) was 30 / 70, to prepare a coating liquid (b-3).

[0162] (Preparation of polyvalent metal compound dispersion (z-1)) For the dispersion of polyvalent metal compounds, 30 parts of ZnO (FINEX-50, manufactured by Sakai Chemical Industry Co., Ltd.) with a primary particle size of 20 nm, 3.8 parts of an aqueous solution of ammonium polyacrylate (A-30SL, manufactured by Toagosei Co., Ltd.), and 62.5 parts of water were mixed, and the mixture was dispersed for 1 hour in a bead mill (Ultra Aspek Mill UAM-015 manufactured by Kotobuki Co., Ltd.) using zirconia beads with a diameter of 0.3 mm. The beads were then sieved to obtain a polyvalent metal compound dispersion (z-1) with a solids concentration of 31.5%.

[0163] (Preparation of polyvalent metal compound dispersion (z-2)) For the dispersion of the polyvalent metal compound, 24 parts of ZnO (FINEX-50, manufactured by Sakai Chemical Industry Co., Ltd.) having a primary particle diameter of 20 nm was mixed with 76 parts of methyl ethyl ketone (MEK), and the mixture was dispersed in a bead mill using zirconia beads having a diameter of 0.3 mm for 1 hour. The beads were then sieved to obtain a polyvalent metal compound dispersion (z-2) having a solids concentration of 24%.

[0164] (Preparation of coating solution (b-4) for (B layer)) 68.8 parts of water, 20.0 parts of isopropyl alcohol (IPA), 10.7 parts of an aqueous solution of ammonium polyacrylate (A-30, Toagosei Co., Ltd.), and 0.7 parts of a polyvalent metal compound dispersion (z-1) were added and stirred for 1 hour to obtain a coating agent (b-4).

[0165] (Adjustment of coating solution (b-5) for (B layer) and (D layer)) 68.3 parts of water, 18.7 parts of isopropyl alcohol (IPA), 10.7 parts of an aqueous solution of ammonium polyacrylate (A-30, Toagosei Co., Ltd.), and 2.3 parts of a polyvalent metal compound dispersion (z-1) were added and stirred for 1 hour to obtain a coating agent (b-5).

[0166] (Preparation of coating solution (b-6) for (B layer)) 62.2 parts of water, 23.0 parts of isopropyl alcohol (IPA), 10.0 parts of an aqueous solution of ammonium polyacrylate (A-30, Toagosei Co., Ltd.), and 4.8 parts of a polyvalent metal compound dispersion (z-1) were added and stirred for 1 hour to obtain a coating agent (b-6).

[0167] (Adjustment of coating solution (b-7) for (B layer) and (D layer)) 65.0 parts of water, 17.0 parts of isopropyl alcohol (IPA), 9.0 parts of an aqueous solution of ammonium polyacrylate (A-30, Toagosei Co., Ltd.), and 9.0 parts of a polyvalent metal compound dispersion (z-1) were added and stirred for 1 hour to obtain a coating agent (b-7).

[0168] (Adjustment of coating solution (b-8) for (B layer)) 68.5 parts of water, 18.0 parts of isopropyl alcohol (IPA), 11.0 parts of an aqueous solution of ammonium polyacrylate (A-30, Toagosei Co., Ltd.), 2.3 parts of a polyvalent metal compound dispersion (z-1), and 0.2 parts of glycerin (Kanto Chemical Co., Ltd.) were added and stirred for 1 hour to obtain a coating agent (b-8).

[0169] (Preparation of coating solution (b-9) for (B layer)) Polyacrylic acid (PAA) (A-10H, Toagosei Co., Ltd.) was diluted with water to a solid content of 3%, to obtain a coating agent (b-9).

[0170] (Adjustment of coating solution (b-10) for (B layer)) Polyacrylic acid (PAA) (AC-10L, Toagosei Co., Ltd.) was diluted with water to a solid content of 3%, to obtain a coating agent (b-10).

[0171] (Preparation of coating solution (b-11) for (B layer)) Polyacrylic acid (PAA) (AC-10P, Toagosei Co., Ltd.) was diluted with water to a solid content of 3%, to obtain a coating agent (b-11).

[0172] (Preparation of coating solution (d-1) for (D layer)) 39 parts of the polyvalent metal compound dispersion liquid (z-2), 1 part of the polyether polyurethane polyol resin solution A, and 60 parts of methyl ethyl ketone (MEK) were added and stirred for 1 hour to obtain a coating agent (d-1). The polyether polyurethane polyol resin solution A used was obtained as follows. A reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, and a rectifying tube was charged with 213.7 parts of polypropylene glycol (hereinafter sometimes abbreviated as PPG) having a molecular weight of 400 with two functionalities, 225.2 parts of PPG having a molecular weight of 700 with two functionalities, 69.0 parts of PPG having a molecular weight of 2000 with two functionalities, and 41.1 parts of PPG having a molecular weight of 430 with three functionalities, and 152.6 parts of tolylene diisocyanate were added while stirring. After reaching 90 ° C, 306.0 parts of ethyl acetate were added, and the reaction temperature was maintained at 90 ° C. to synthesize. It was confirmed that the NCO (%) was 0.1% or less and the viscosity with a B-type viscometer was within 2000 to 3000 mPa, and a polyether polyurethane polyol resin solution A was obtained.

[0173] Example 1 (Preparation of gas barrier laminate) Corona treatment at 100W / (m 2 The coating liquid (b-1) was applied onto the (A) layer, which had been applied with an irradiation dose of 1000 nm / min, using bar coater #3, and then dried for 1 minute in a hot air dryer set at 80°C to form the (B) layer, which was then used as a gas barrier laminate.

[0174] (Production of packaging materials) Dikdry LX-830 and KW-75 (both from DIC Corporation) were mixed in a mixing ratio of 10 / 1.5, and ethyl acetate was added so that the non-volatile content was 25% to obtain an adhesive. The adhesive was then applied to the (B) layer of the prepared gas barrier laminate using a bar coater #8, and the dilution solvent was evaporated using a dryer set at a temperature of 50°C, after which it was laminated with a non-oriented polypropylene film (CPP film, Toyobo Co., Ltd., P1128). Aging was performed for 3 days at 40°C to obtain a packaging material [(A) layer (substrate is OPP film) / (B) layer / adhesive / CPP film].

[0175] (Examples 2 to 40) The same procedures as in Example 1 were carried out except that the surface treatment method for the inorganic layer (A) of Example 1 and the (B) layer were changed as shown in Tables 1 to 8, to obtain gas barrier laminates and packaging materials of Examples 2 to 40, respectively.

[0176] The evaluation results are shown in Tables 1 to 8.

[0177] [Table 1]

[0178] [Table 2]

[0179] [Table 3]

[0180] [Table 4]

[0181] [Table 5]

[0182] [Table 6]

[0183] [Table 7]

[0184] [Table 8]

[0185] (Example 41) (Preparation of gas barrier laminate) Corona treatment at 100W / (m 2Onto the (A) layer, which had been exposed to an irradiation dose of 1000 nm / min, a coating solution (b-9) was applied using a bar coater #3 and dried for 1 minute in a hot air dryer set at 80°C to form a (B) layer. Thereafter, a coating solution (b-5) was applied using a bar coater #3 and dried for 1 minute in a hot air dryer set at 80°C to form a (D) layer, which was used as a gas barrier laminate.

[0186] (Production of packaging materials) Dikdry LX-830 and KW-75 (both from DIC Corporation) were mixed in a mixing ratio of 10 / 1.5, and ethyl acetate was added so that the non-volatile content was 25% to obtain an adhesive. The adhesive was then applied to the (D) layer of the gas barrier laminate produced using a bar coater #8, and the dilution solvent was evaporated using a dryer set at a temperature of 50°C, after which it was laminated with a non-oriented polypropylene film (CPP film, Toyobo Co., Ltd., P1128). Aging was performed for 3 days at 40°C to obtain a packaging material [(A) layer (substrate is OPP film) / (B) layer / (D) layer / adhesive / CPP film].

[0187] (Examples 42 to 65) The same procedure as in Example 42 was performed except that the surface treatment method for the inorganic layer (A) of Example 41 and the (B) and (D) layers were changed as shown in Tables 9 to 13, respectively, to obtain gas barrier laminates and packaging materials of Examples 42 to 65, respectively.

[0188] [Table 9]

[0189] [Table 10]

[0190] [Table 11]

[0191] [Table 12]

[0192] [Table 13]

[0193] (Comparative Examples 1 to 14) The same procedure as in Example 1 was carried out except that the surface treatment of the inorganic layer of Layer (A) and Layer (B) were changed as shown in the table, to obtain gas barrier laminates and packaging materials of Comparative Examples 1 to 14, respectively.

[0194] The evaluation results are shown in Tables 14 to 16.

[0195] [Table 14]

[0196] [Table 15]

[0197] [Table 16]

[0198] In Examples 1 to 65, gas barrier laminates having excellent adhesion, laminate strength, and gas barrier properties were produced. On the other hand, in Comparative Examples 1 to 14, which do not satisfy the requirements of the present invention, sufficient adhesion, lamination strength, and gas barrier properties were not obtained. Since each Example and Comparative Example has a common CPP film, the differences in adhesion, lamination strength, and gas barrier properties observed between the Examples and Comparative Examples are considered to be due to differences in the configurations of the laminate and packaging material. From the above results, it was confirmed that the gas barrier laminate and packaging material having the configuration of the present invention have good adhesion, laminate strength, and gas barrier properties.

Claims

1. (A) a layer (A) made of a substrate having an inorganic layer formed on at least one surface thereof; (B) a layer (B) containing a water-soluble polymer; In the (A) layer, the surface on which the inorganic layer is formed has a static contact angle with water at 25° C. of 20 degrees or more and 80 degrees or less, and / or the surface free energy of the surface on which the inorganic layer is formed is 41 mN / m or more and 75 mN / m or less. the water-soluble polymer in the layer (B) is a (meth)acrylic acid polymer and / or a salt of an acrylic acid polymer, The layer (B) contains a metal alkoxide, a hydrolysate of a metal alkoxide, and / or a polyvalent metal compound. A method for producing a gas barrier laminate, comprising the steps of: A step 1 of subjecting the inorganic layer of layer (A) made of a substrate having an inorganic layer formed on at least one surface thereof to a corona treatment, an ozone treatment, a plasma treatment, an ultraviolet irradiation treatment, or an excimer UV treatment; A method for producing a gas barrier laminate, comprising: providing a layer (B) containing a water-soluble polymer on the layer (A); and, in this order, performing step 2.

2. (A) a layer (A) made of a substrate having an inorganic layer formed on at least one surface thereof; (B) a layer (B) containing a water-soluble polymer; (D) A layer (D) having a polyvalent metal compound adjacent to the layer (B). and In the (A) layer, the surface on which the inorganic layer is formed has a static contact angle with water at 25° C. of 20 degrees or more and 80 degrees or less, and / or the surface free energy of the surface on which the inorganic layer is formed is 41 mN / m or more and 75 mN / m or less. The water-soluble polymer in the layer (B) is a (meth)acrylic acid polymer and / or a salt of an acrylic acid polymer. A method for producing a gas barrier laminate, comprising the steps of: A step 1 of subjecting the inorganic layer of layer (A) made of a substrate having an inorganic layer formed on at least one surface thereof to a corona treatment, an ozone treatment, a plasma treatment, an ultraviolet irradiation treatment, or an excimer UV treatment; A method for producing a gas barrier laminate, comprising: providing a layer (B) containing a water-soluble polymer on the layer (A); and, in this order, performing step 2.

3. In the layer (D) containing the polyvalent metal compound, the polyvalent metal compound is zinc oxide, magnesium oxide, and / or calcium oxide; The method for producing a gas barrier laminate according to claim 2, further comprising: a (meth)acrylic acid polymer; a salt of an acrylic acid polymer; and / or a polyurethane polyol.

4. 3. The method for producing a gas barrier laminate according to claim 1, wherein the inorganic layer in the layer (A) is formed from one or more inorganic substances selected from the group consisting of aluminum oxide, silicon oxide, aluminum, zinc oxide, and magnesium oxide.

5. The method for producing a gas barrier laminate according to claim 1 or 2, wherein in the layer (A), the inorganic layer has been subjected to a corona treatment, an ozone treatment, a plasma treatment, an ultraviolet ray irradiation treatment, or an excimer UV treatment.

6. A method for producing a packaging material using the gas barrier laminate according to claim 1 or 2.

7. A method for producing a packaging material, comprising laminating the gas barrier laminate according to claim 1 or 2 and a second substrate with an adhesive.

Citation Information

Patent Citations

  • Air-blocking and water-blocking laminated film for packaging and application of air-blocking and water-blocking laminated film in food packaging

    CN114479153A

  • Transparent barrier film

    JP1999322981A

  • Barrier film and laminate employing the same

    JP2000127286A

  • Aluminum oxide vapor deposited polyolefin film

    JP2000185378A

  • Laminate and packaging material comprising the same

    JP2003311872A